Finite element analysis on pepper brick strength - Loh, E.K (Universiti Malaysia Sarawak, UNIMAS, 2009)
This thesis presents the application of Simulia Abaqus/CAE to model three dimensional pepper waste mixed brick and to do finite element analysis in order to find the effect of pores percentage on the internal stress distribution. This brick will be modeled as elastic homogeneous isotropic material with random distribution of 0, 2, 5 and 10 Wt. % voids to represent the pores. Data are gathered using two methods; three sets of horizontal nodes and another two sets for vertical nodes. Data gathered for each type of pore composition will be compared to von Mises stress of corresponding node from 0 Wt. % brick as the reference maximum stress. Failure probability will be analyzed for each set of data and arranged in a table. This analysis method will be used to determine the best pore composition for minimum failure probability with most porosity as possible. Result is consistent with actual experimental data which suggest 5 Wt. % brick as the best choice.